Development of Listening Skills Evaluation Instruments | Pengembangan Instrumen Evaluasi Keterampilan Menyimak - Sherly Yustuti; Masrun Masrun; Hikmah Hikmah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to determine the development of listening skills evaluation instruments students of class VIII MTs PP. Muallimin Muhammadiyah Bangkinang City. This research method is descriptive qualitative. This study describes the development of a listening skill evaluation instrument. The results showed that to measure listening skills, apart from being seen from the side of communication, listening skills can also be measured through evaluation of learning with instruments or various tests. In maharahh istima’ there area 3 levels, namely beginner level (mubtadi’), intermediate level (muttawassit) and advanced level (mutaqoddim). The Arabic listening skill test is divided into two parts, namely: a language sound test (iktibar al-ashwat) and a test for understanding the text heard (fahm al- masmu’). The language sound test includes repeating the spoken word, identifying sounds, distinguishing sounds of similar letters, identifying in terms of meaning, identifying sounds based on nahwu rules, and distinguishing between muzakkar and mu’annas. Meanwhile, what is included is an understanding test of what is heard, namely responding to speech in the form of motion sentences, understanding a simple text in the form of dialogue, understanding a simple text in narrative form and writing numbers.